2018
DOI: 10.1136/gutjnl-2018-316155
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota metabolites, amino acid metabolites and improvements in insulin sensitivity and glucose metabolism: the POUNDS Lost trial

Abstract: ObjectiveAlterations in gut microbiota have been linked to host insulin resistance, diabetes and impaired amino acid metabolism. We investigated whether changes in gut microbiota-dependent metabolite of trimethylamine N-oxide (TMAO) and its nutrient precursors (choline and L-carnitine) were associated with improvements in glucose metabolism and diabetes-related amino acids in a weight-loss diet intervention.DesignWe included 504 overweight and obese adults who were randomly assigned to one of four energy-reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(98 citation statements)
references
References 52 publications
4
92
0
2
Order By: Relevance
“…The POUNDS Lost Trial included 510 overweight and obese individuals exposed to a low-calorie diet for two years and found that a decrease in choline and l -carnitine levels was significantly related to weight loss, indicating it might serve as a predictive marker of response to weight-loss treatment [ 58 , 59 , 60 ]. The same study documented a significant improvement in IR associated with decreases in choline and l -carnitine [ 61 ]. Moreover, non-esterified fatty acids are known to induce IR and thus impair β-cell function [ 62 ].…”
Section: Epigenetics Microbiota and T2dmmentioning
confidence: 99%
“…The POUNDS Lost Trial included 510 overweight and obese individuals exposed to a low-calorie diet for two years and found that a decrease in choline and l -carnitine levels was significantly related to weight loss, indicating it might serve as a predictive marker of response to weight-loss treatment [ 58 , 59 , 60 ]. The same study documented a significant improvement in IR associated with decreases in choline and l -carnitine [ 61 ]. Moreover, non-esterified fatty acids are known to induce IR and thus impair β-cell function [ 62 ].…”
Section: Epigenetics Microbiota and T2dmmentioning
confidence: 99%
“…Trimethylamine N-oxide (TMAO) is a bacterial-derived metabolite that has been strongly associated with cardiovascular risks in both human and animal studies 162,[169][170][171] . Choline and l-carnitine are the major precursors of TMAO, and they are highly abundant in the Western diet, which is rich in red meat, dairy products, eggs and fish (Fig.…”
Section: Specific Drugs To Alter Microbial Metabolismmentioning
confidence: 99%
“…The intestinal barrier is considered a functional, immunological, and anatomical unit, separating the intestinal lumen from circulating blood, preventing bacterial adherence and transport regulation. Methanolamine and other intestinal metabolites reach almost all tissues as small molecules thus affecting both neurohormonal and peripheral regulatory mechanisms [ 17 ].…”
Section: Microbiome Compositionmentioning
confidence: 99%